Corona ageing characteristics of composite insulators based on orthogonal experiment. Issue 2 (1st March 2019) - Liang, Ying; Gao, Ting; Dong, Pingping; Gao, Lijuan
Abstract : To study effects of pressure, humidity and aging time on the corona aging process, aging characteristics of silicone rubber composite insulators were researched by orthogonal tests. The test platform of adjustable pressure and humidity was constructed. TSC, SEM and FTIR tests were selected for aged samples. By the range analysis, it showed that the effect of pressure on trapped charges was related to humidity and aging time. There were more trapped charges when the humidity was higher, and the influence of humidity was more obvious along with the longer aging time at a low pressure. As the pressure increased, however, the effect of humidity on trapped charges was gradually reduced. But the influence of aging time was more significant, while aged degree of silicone rubber was deepened with increasing aging time. Furthermore, the aging state of materials was the collaboration effect of charged particles and nitric acid. Moreover, it could be seen from TSC, SEM and FTIR tests, sorting results of aging states were inconsistent. Results showed that the TSC test was comprehensively embodied the corona aging characteristics caused by physical and chemical defects. Therefore, results of TSC tests could be selected as an effective criterion for aging evaluations.